2018
DOI: 10.1146/annurev-soc-060116-053653
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Credit in Comparative Perspective

Abstract: We review the literature in sociology and related fields on the fast global growth of consumer credit and debt and the possible explanations for this expansion. We describe the ways people interact with the strongly segmented consumer credit system around the world—more specifically, the way they access credit and the way they are held accountable for their debt. We then report on research on two areas in which consumer credit is consequential: its effects on social relations and on physical and mental health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 143 publications
(90 reference statements)
2
20
0
Order By: Relevance
“…Young people of today are taking debt at unprecedented levels [ 1 3 ]. General deregulation has made consumer lending attractive for various financial institutions throughout Western countries, including predatory and fringe banking agencies [ 4 , 5 ]. To this effect, the current young generation has been even labeled as a “generation indebted” in the USA [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people of today are taking debt at unprecedented levels [ 1 3 ]. General deregulation has made consumer lending attractive for various financial institutions throughout Western countries, including predatory and fringe banking agencies [ 4 , 5 ]. To this effect, the current young generation has been even labeled as a “generation indebted” in the USA [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variation between different countries in how insolvency is handled and regulated. Nordic countries, such as Finland or Sweden, take the pro-creditor stance [ 4 , 40 ]. In Finland, for instance, personal bankruptcy is not possible, and debt remains enforceable for 15 years in commercial cases and 20 years in criminal cases.…”
Section: Introductionmentioning
confidence: 99%
“…This process took shape roughly around the 1980s in the developed world, where financial markets reached a stage of impressive innovation, complexity and dynamism led by liberalization and deregulation. Nowadays, astonishing levels of credit, debts, stocks and insurances are traded on a real-time basis with the help of information technologies and risk-management techniques, becoming a global phenomenon (Rona-Tas & Guseva, 2018). This phenomenon was to a great extent driven by the fact that non-financial firms turn to finance as a source of profits.…”
Section: Financialization and The Fictitious Commodity Of Money Under Neoliberalismmentioning
confidence: 99%
“…Increasingly, these consumer credit rating systems rely on algorithms and big data to generate scores of individuals (Marron, 2009;Rona-Tas & Guseva, 2018). Through the use of data, individuals become relegated to mere numbers (Rona-Tas & Guseva, 2018). In this way, banks are able to reduce uncertainty by associating individuals with ratings of risk factors, allowing them to decide credit limits more accurately (Guseva & Rona-Tas, 2001).…”
Section: Credit Rating Systems and Moralization Of Societymentioning
confidence: 99%
“…It has been suggested that individuals with bad credit and financial constraints are likely to experience limited career choices, which would lead to restrictions on social mobility (Shao, McKinney, & Shao, ). Increasingly, these consumer credit rating systems rely on algorithms and big data to generate scores of individuals (Marron, ; Rona‐Tas & Guseva, ). Through the use of data, individuals become relegated to mere numbers (Rona‐Tas & Guseva, ).…”
Section: Credit Rating Systems and Moralization Of Societymentioning
confidence: 99%